2019
DOI: 10.1016/j.oregeorev.2019.102955
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation and measurement of Au and Ag in epithermal mineralizing fluids

Abstract: Colloidal gold particles have been observed in c. 300 O C low salinity fluids from the Arapucandere intermediate sulphidation epithermal base-metal-Au deposit in NW Turkey. This is the first time colloidal gold has been recorded in an ancient mineralizing fluid. Growth, in veins, of large euhedral quartz crystals, after the deposition of sulphides, occurred in a number of stages from the introduction of fresh pulses of fluid. The quartz overgrowths have a fibrous texture which facilitated trapping of large elo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 75 publications
2
8
0
1
Order By: Relevance
“…2). Similar signal shapes were observed for gold in fluid inclusions at the Arapucandere epithermal deposit, where in open fluid inclusions the 1 µm to 100 nm particulate gold was detected using a scanning electron microscopy (SEM) 14 . In this study particulate gold was not observed in any open fluid inclusions using SEM, suggesting the particles must be much smaller than the limit of detection.…”
Section: Laser Ablation Inductively Coupled Plasma Mass Spectrometrysupporting
confidence: 65%
See 1 more Smart Citation
“…2). Similar signal shapes were observed for gold in fluid inclusions at the Arapucandere epithermal deposit, where in open fluid inclusions the 1 µm to 100 nm particulate gold was detected using a scanning electron microscopy (SEM) 14 . In this study particulate gold was not observed in any open fluid inclusions using SEM, suggesting the particles must be much smaller than the limit of detection.…”
Section: Laser Ablation Inductively Coupled Plasma Mass Spectrometrysupporting
confidence: 65%
“…Direct evidence of gold colloids in hydrothermal fluids, was first reported 34,35 in fluids from high temperature black smokers exhaled into the cold seawater. However, the first evidence of transportation of colloidal gold particles in and trapped in the fluid inclusions of high temperature ore fluids was from the Arapucandere base-metal ± gold deposit 14 . Cao et al 36 have also suggested that gold nanoparticles can be transported to the surface in gas from the Earth's interior.…”
Section: Discussionmentioning
confidence: 99%
“…hydrotherms, saturated with ions of chlorine, sodium, magnesium, and iron at temperatures from 340 to 158 • C. A low level of salt concentration in hydrothermal solutions is characteristic of epithermal systems. This may be a consequence of the condensation of magmatic vapor [53][54][55], and the boiling process [56,57]. Most FI were trapped in two temperature intervals, which show that the first ore-forming stage contained two substages: 300-275 • C and 175-150 • C. It was found that three kinds of quartz filling ore formations were formed successively on cooling of the system: (1) light, medium-to fine-grained quartz (Type 1), building quartz-adularia lode-veinlet aggregates of the colloform-banded and crustified-platy structures (Sample 016c) (Figure 2a,b; Table 5), was formed at 340 to 192 • C; (2) fine-grained quartz (Type 2), forming aggregates of massive, brecciform, and porous structures, with mostly galena mineralization (Sample 053) (Figure 2c,d; Table 5), at 307 to 172 • C; (3) grey, cryptocrystalline (Type 3), which builds dark rhythms of colloform-banded and banded aggregates, serves as the cementing material for breccia formation, and contains submicroscopic impregnations of gold and silver minerals (Sample 1014B) (Figure 2e,f; Table 5), at 205 to 158 • C. In ore-forming solutions, trapped by the light quartz FI (Type 1), salt concentration is seven times as large (Table 5; Figure 7) as that in the grey quartz FI (Type 3).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, low-density CO 2 with minor N 2 and CH 4 (Figure 6) was found only in the light quartz FI, which means that in the initial period, up to approximately 300 • C, the ore-forming fluid contained low-density gases. Vapor phases, according to [57,58], are capable of transporting gold in the form of colloid particles of heterogeneous trapping. Prokofiev et al [59] determined the presence of gold as nanoparticles in fluid inclusions by optical and spectroscopic methods.…”
Section: Discussionmentioning
confidence: 99%
“…Deposits in the Biga Peninsula can either have fluid inclusions with a dominantly high homogenization temperature and low salinity, in the deposits that are gold resources or with similar high homogenization temperatures, but a mixed range of salinities, as we have presented in this study, in deposits that are a base-metal resource with lesser amounts of gold (Table 1). Low salinity fluid inclusions from the Arapuçandere deposit, which is similar to Koru, are interpreted to be derived from magmatic vapors, following a study by Banks et al (2019). The high homogenization temperature, low salinity fluids have gold and silver concentrations up to 100's of ppm and gold particles can be observed in all of the inclusions.…”
Section: Temperature-salinity Variabilitymentioning
confidence: 96%